Left bundle branch pacing after transcatheter aortic valve implantation. Initial experience of a center. (3rd October 2022) - Vela Martin, P; Arellano Serrano, C; Castro Urda, V; Garcia Rodriguez, D; Hernandez Terciado, F; Garcia-Izquierdo, E; De Castro Campos, D; Jimenez Sanchez, D; Matutano Munoz, A; Toquero Ramos, J; Garcia-Touchard, A; Fernandez Lozano, I; et al.
Abstract: Introduction: Permanent pacing is often needed in patients with severe aortic stenosis undergoing transcatheter aortic valve implantation (TAVI) due to new onset conduction disorders. Nevertheless, continuous right ventricular pacing may deteriorate left ventricular ejection fraction (LVEF) and lead to poor outcomes. Thus, in last years, more physiological forms of pacing, such as left bundle branch pacing (LBBP) have been developed to prevent pacing induced cardiomyopathy. Purpose: The aim of our study is to describe the initial experience in our center, evaluate the safety and feasibility of LBBP after TAVI and describe electrophysiological outcomes in the first months of follow-up. Methods: We designed a prospective registry that collected all patients from the TAVI program of our center who developed conduction abnormalities in the immediate postoperative and received LBBP. We analyzed baseline characteristics, complications and procedure time, electrophysiological parameters after the procedure and final QRS interval. During follow-up LVEF, electrophysiological parameters and adverse clinical events (readmissions for heart failure, cardiovascular mortality and all-cause of mortality) were also evaluated at 3rd, 6th and 12th month. Results: Between January 2020 and January 2022, twenty patients who developed conduction abnormalities after TAVI underwent LBBP. Seven patients (35%) had a complete atrioventricular block, two patients (10%) alternating bundle branch block and 11 (55%) had a new left bundle branch block. HV electrophysiology study was performed in 8 patients, with a median value of 68ms (66–72). Of the 20 patients, 3 out of 4 patients were male and had history of hypertension. 40% had previous ischemic heart disease and one patient had transthyretin cardiac amyloidosis. Median age was 79 years-old (76–83.5). Balloon-expandable prosthesis was implanted in 11 patients while 9 received a self-expandable prosthesis. Median basal LVEF was 59% (41.5–60) and median NTproBNP was 1722pg/ml (535–5848). LBBP was successful in all of the 20 patients. The median time of the procedure was 60 minutes (45–80) without suffering any complications. The median QRS interval before the procedure was 155ms (140–158) and 116ms (105–125) post-implant. To date, two patients have died of non-cardiac cause 3 and 8 months after LBBP. There have been no readmissions for heart failure. LVEF (pre and post-LBBP) and electrophysiological parameters post-implant and three-month follow-up are shown in Table 1. Conclusions: In our experience, LBBP after TAVI is a safe and feasible procedure. Despite the small sample size and short follow-up period, our first results indicate stability of LVEF and pacemaker parameters. Funding Acknowledgement: Type of funding sources: None.